2018
DOI: 10.1101/350637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute inflammation sensitizes knee-innervating sensory neurons and decreases mouse digging behavior in a TRPV1-dependent manner

Abstract: threshold, as well as increased GABA and capsaicin sensitivity, but have unaltered acid sensitivity. 10The inflammation-induced sensitization of knee neurons persisted for 24-hours in culture, but was

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 75 publications
6
25
1
Order By: Relevance
“…Consistent with our hypothesis, when AAV‐PHP.S‐CAG‐dTomato and the commonly used retrograde tracer, fast blue, were co‐injected unilaterally into 1 knee in mice (n = 3, all female), we observed both fast blue and virus labeling (Figure A). Comparable to findings of previous studies that used fast blue and other retrograde tracers , we observed a similar proportion of labeling in the lumbar DRG neurons with fast blue and AAV‐PHP.S‐CAG‐dTomato (Figure B). Across L2–L5 DRG, there was ~40% co‐labeling of neurons with fast blue and AAV‐PHP.S‐CAG‐dTomato, which suggests that neither retrograde tracer is able to label the entire knee neuron population (Figure C and Supplementary Figure 1, http://onlinelibrary.wiley.com/doi/10.1002/art.41314/abstract).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Consistent with our hypothesis, when AAV‐PHP.S‐CAG‐dTomato and the commonly used retrograde tracer, fast blue, were co‐injected unilaterally into 1 knee in mice (n = 3, all female), we observed both fast blue and virus labeling (Figure A). Comparable to findings of previous studies that used fast blue and other retrograde tracers , we observed a similar proportion of labeling in the lumbar DRG neurons with fast blue and AAV‐PHP.S‐CAG‐dTomato (Figure B). Across L2–L5 DRG, there was ~40% co‐labeling of neurons with fast blue and AAV‐PHP.S‐CAG‐dTomato, which suggests that neither retrograde tracer is able to label the entire knee neuron population (Figure C and Supplementary Figure 1, http://onlinelibrary.wiley.com/doi/10.1002/art.41314/abstract).…”
Section: Resultssupporting
confidence: 88%
“…Based on previous studies , we hypothesized that the increased excitability of knee‐innervating neurons in vitro via the G q ‐DREADD system would cause pain‐like behavior in mice in vivo, which was tested by assessing digging behavior (a measure of spontaneous pain as previously described ), dynamic weight bearing, and rotarod behavior (a measure of motor coordination ) (Figure D). Three weeks after virus injection into both knee joints, mice injected with vehicle or C21 (n = 4 male and 4 female mice in each group) did not show significant changes in digging behavior (mean ± SEM digging duration pre‐vehicle 31.6 ± 3.7 seconds versus post‐vehicle 21.3 ± 4.4 seconds; mean ± SEM digging duration pre‐C21 25.2 ± 4.9 seconds versus post‐C21 32.7 ± 4.7 seconds; mean ± SEM number of burrows pre‐vehicle 4.6 ± 0.5 versus post‐vehicle 3.5 ± 0.4; mean ± SEM number of burrows pre‐C21 3.9 ± 0.7 versus post‐C21 3.6 ± 0.5) (Figures E and F) or weight bearing (mean ± SEM front paw to rear paw weight ratio pre‐vehicle 0.5 ± 0.02 versus post‐vehicle 0.5 ± 0.04; mean ± SEM front paw to rear paw weight ratio pre‐C21 0.4 ± 0.06 versus post‐C21 0.4 ± 0.03) (Figures G and H).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations